But the Pain Remains: A Response to Verpaelst - Raymond, Marie-Hélène (BioéthiqueOnline)

(untitled) (BioéthiqueOnline, 2015)
People who experience chronic pain often refrain from expressing their pain overtly due to fear of stigmatization. Health professionals working with these persons may also find it challenging to face the persistent nature of their clients’ pain. Through his painting, Verpaelst helps to overcome these difficulties.